2021
DOI: 10.2106/jbjs.oa.20.00167
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Lumbosacral Anatomy and Vertebral Numbering in Patients with Thoracolumbar and/or Lumbosacral Transitional Vertebrae

Abstract: Background:The presence of a thoracolumbar transitional vertebra (TLTV) and/or lumbosacral transitional vertebra (LSTV) may cause wrong-site surgery and problems while measuring spinopelvic parameters, including pelvic incidence and lumbar lordosis. The Castellvi classification of LSTV addresses coronal images but not sagittal or axial images. Therefore, it is unclear how LSTV differs from the normal lumbosacral anatomy. We aimed to investigate the lumbosacral anatomy and vertebral numbering in patients with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…Secondly, this study excluded volunteers with an abnormal vertebral count or transitional anatomy. Previous literature has shown that a sizeable portion of people exhibits such abnormal or transitional vertebral anatomy 21–23. Thus, the findings reported in this study apply to asymptomatic volunteers but not to those with abnormal or transitional vertebral anatomy.…”
Section: Discussionmentioning
confidence: 49%
“…Secondly, this study excluded volunteers with an abnormal vertebral count or transitional anatomy. Previous literature has shown that a sizeable portion of people exhibits such abnormal or transitional vertebral anatomy 21–23. Thus, the findings reported in this study apply to asymptomatic volunteers but not to those with abnormal or transitional vertebral anatomy.…”
Section: Discussionmentioning
confidence: 49%
“…Scans were excluded if there was any evidence of previous spinal, pelvic or hip joint surgery or fracture, tumor or infection that could preclude analysis of either vertebral, or pelvic parameters. Scans were also excluded if there was an abnormal vertebral body count of if there was transitional anatomy as this could influence the pelvic parameters (Tatara et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Результаты мультиспиральной компьютерной томографии более наглядны, и на их основании, как правило, выносят заключение о типе переходных позвонков, в том числе в грудопоясничном отделе [32,50,51]. По мнению Y. Tatar и соавт., аксиальные сканы иллюстрируют морфологические особенности существующей патологии, в то время как сагиттальные изображения дают информацию о пояснично-крестцовой анатомии [52]. Применение в диагностических целях магнитно-резонансной томографии позволяет получить достоверную информацию о наличии и тяжести экстрафораминального стеноза, импиджмента и отёка корешков спинномозговых нервов L 4 , L 5 , S 1 [53][54][55].…”
Section: объективная диагностикаunclassified